Managing the delivery of venous leg ulcer services: A willingness to pay study - Nyantara Wickramasekera; Simon Palfreyman; Elizabeth Lumley; Arvind Dosanjh; Phil Shackley (Health Science Reports, 2022)
Abstract Background and Aims There is widespread variation in venous leg ulcer (VLU) wound care contributing to inadequate service provision resulting in poor outcomes to patients. Little has been published on the perspectives of where treatments should be carried out. The aim of the study was to quantify respondents' preferences for the preferred place of treatment for VLU. Methods A UK general population sample was interviewed to elicit preferences for clinic or home care treatment using the willingness to pay elicitation method. Participants were presented with two vignettes describing clinic or home care of VLU, and were asked to select the treatment process that they preferred and provide a detailed explanation for selecting that choice. Then they were asked to state their maximum hypothetical amounts that they were willing to pay for the treatment processes. Results One hundred fifty‐four participants completed the interviews. Respondents were willing to pay £498.96 to receive VLU treatment at a clinic and £505.60 to receive care at home. This difference between the clinic compared to home care was not statistically significant. Advantages of clinic care include being able to book an appointment allowing participants to plan events around the booking and for home care the convenience for those with impaired mobility who may have difficulty traveling. Conclusions The results show that respondents placed an equal valuation on the place of treatment suggesting no strong preference for either home or clinic care. However, qualitative findings emphasized that impaired mobility may be a barrier to accessing VLU services for some therefore, individuals should be given the choice to select their preferred setting to receive treatment where possible.